Kerukunan Hidup Beragama (Studi Tentang Realitas Hubungan Sosial Antar Umat Beragama di Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat) - Rasito, Rasito (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2007)
This research is aimed at knowing the interrelation of religion condition among their respective adherents, potential conflicts, the tendency in religion interrelationship, the local institutions which are dominant in keeping the harmonization of the interrelationship omong the religion, and the government policies bringing abottt the conducive atmosphere for creating the social integration and interrelationship among the society. This research employs the qualitative as well as quantitative approach. The level of relationship among the aclherents of respective religion to others is obviously dynamic. Some of the influential factors affecting the tide of these relationships in Kecamatan Tungkal llir are malfunction of houses as churches, massive uncontrolled expansion of religion (propaganda), and the establishrnent of worshipping houses. The writer recommends, at last, that there is a need to socialize to the respective religion of how to establish the worshipping houses, to make an intensive dialog, and to empower the Communication Forum for Â Religion Propagonda.